Are Scale Insects in the Homoptera or Hemiptera; do they comprise a Superfamily or a Suborder? (Bollettino di zoologia agraria e bachicoltura, 2024)
For some time, I have noted discrepancies in the titles of papers dealing with scale insects. For example articles listed in the March 2000 issue of The Scale included in their titles various higher category taxonomic names: e.g., Homoptera in 48 titles from 18 countries, and Hemiptera in 28 titles from 12 countries. In the March 2001 issue ofThe Scale, we found Homoptera in 85 titles from 25 countries and Hemiptera in 33 titles from 14 countries. It must be confusin for catalogers that encounter scale insects placed in either the superfamily Coccoidea or the suborder Coccinea within the same article titles. In the future, our successors may choose to adopt the already proposed order name Coccura. Are we going to keep Homoptera or Hemiptera, or abandon both and use only Sternorrhyncha or Rhynchota, already used by some, until this issue is scientifically clarified? It should be the responsibility of the public forum of ISSIS-IX to debate and attempt to standardize the nomenclature to be used in the future. The previous eight symposia brought us together in the co-operative spirit that has always allowed us to co-ordinate major projects to avoid duplication and has led to general progress in coccidology. Let's continue in that spirit.
Keywords: Coccoidea; Coccinea; Coccura; Sternorrhyncha; nomenclature